PARTISIPASI MASYARAKAT DALAM PEMAHAMAN POLITIK TERHADAP PERSIAPAN PEMILU 2024 - Aisyah Nurul Aeni; Cindi Eva Sundari; Rahmat Saputra (Abdi Bhara, 2023)
Indonesia is a country that is often oscillated byrepeated large-scale political changes. Democracy in thisbeloved country has also experienced significant ups and downs.Not unlike the general trend in many countries, political changesand the ups and downs in the quality of democracy in this countryalso had implications for (and therefore can be observed itsmanifestations in) in the administration of elections, the maincomplaints about the quality of democracy during the New Ordergovernment, among others, were addressed in the holding ofintimidating and fraudulent elections. On the other hand, pridein the reform era has always been attributed to our nation'sability to hold free, honest and fair multi-party elections since1999. Even so, elections in Indonesia are not always easilyunderstood by the public and voters. The ever-changingregulations have greatly contributed to the confusion over ourelectoral systems and procedures. Meanwhile, completeinformation about elections in Indonesia is not always easy tofind. Election contestants can be individuals or political parties,but most importantly political parties. Political parties submitcandidates in elections to be elected by the people.